2011
DOI: 10.1186/1742-2094-8-78
|View full text |Cite
|
Sign up to set email alerts
|

S-Nitrosoglutathione reduces oxidative injury and promotes mechanisms of neurorepair following traumatic brain injury in rats

Abstract: BackgroundTraumatic brain injury (TBI) induces primary and secondary damage in both the endothelium and the brain parenchyma, collectively termed the neurovascular unit. While neurons die quickly by necrosis, a vicious cycle of secondary injury in endothelial cells exacerbates the initial injury in the neurovascular unit following TBI. In activated endothelial cells, excessive superoxide reacts with nitric oxide (NO) to form peroxynitrite. Peroxynitrite has been implicated in blood brain barrier (BBB) leakage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 94 publications
(168 reference statements)
8
107
1
1
Order By: Relevance
“…Although modest inflammation plays a role in neuroprotection in acute insults, chronic inflammation is detrimental to neurogenesis [41]. Previously, we reported that GSNO protects the brain against injuries from ischemia/reperfusion [17, 18], traumatic brain injury [42, 43], and experimental autoimmune encephalomyelitis [19, 44] by inhibiting neural and vascular inflammation. Based on these studies, we investigated whether the GSNO-mediated protective mechanisms involve anti-inflammatory effects in animals with BCCAO.…”
Section: Resultsmentioning
confidence: 99%
“…Although modest inflammation plays a role in neuroprotection in acute insults, chronic inflammation is detrimental to neurogenesis [41]. Previously, we reported that GSNO protects the brain against injuries from ischemia/reperfusion [17, 18], traumatic brain injury [42, 43], and experimental autoimmune encephalomyelitis [19, 44] by inhibiting neural and vascular inflammation. Based on these studies, we investigated whether the GSNO-mediated protective mechanisms involve anti-inflammatory effects in animals with BCCAO.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, PPAR-␥ activators are documented to enhance anti-inflammatory activities in astrocytes and other cell types (64,65). In light of these studies, we conclude that NO signaling in astrocytes is crucial to provide anti-inflammatory and neuroprotective activities in experimental autoimmune encephalomyelitis and traumatic brain injury models (25,26,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…GSNO has recently been reported to regulate various cellular functions (23,38). In addition, earlier we documented that exogenously administered GSNO restores blood brain barrier integrity and attenuates disease severity in experimental autoimmune encephalomyelitis (25,26) and traumatic brain injury (30,31) models. These studies provide evidence that regardless of the excessive expression of inducible nitric-oxide synthase/NO production by activated CNS glial cells in response to inflammatory insult, the exogenously administered GSNO has a tendency to limit the generation of circulating reactive nitrogen species NO/ONOO in vivo (39).…”
Section: S-nitrosothiols Induce Hypertrophic Astrogliosis In Treatedmentioning
confidence: 99%
“…However, recently reported results indicate that these products can be in vivo recycled and transformed back into NO, which represents an important unconventional source of NO outside of the classical L-arginine-NO synthase pathway (Lundberg et al, 2008). Based on the study by Khan et al (2011), both nitrite and nitrate ions may be significant precursors of NO and can increase the NO concentration in brain. SNA F2 was comparatively more stable than GSNO and finally degraded to nitrite and nitrate ions after 10 h (Figure 2).…”
Section: Permeability Studies In the Ussing Chambermentioning
confidence: 99%